The Speaking Performance and Anxiety: A Correlation Study in EFL Senior High School Students in Madiun, East Java - Arifin, Samsul; Rizki Firis Manda , Thoriq (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2021)
This research is conducted to see if there is a significant correlation among the students’ speaking performance and speaking anxiety of eleventh grade students in Madiun, East Java. There were 22 students who participated in this study. The researcher used quantitative research method with correlational research design. The researcher collected the students’ speaking performance through the speaking test using Brown’s speaking assessment and investigated their speaking anxiety using 1-5 Likert-scale questionnaires. The questionnaires were modified from students’ speaking anxiety scale conducted by Woodrow. The data were analyzed using IBM SPSS (Statistical Package for the Social Science) ver 22, specifically on normality and correlation test. The result shows that the correlation coefficient number of -0.766 and sig (2-tailed) at 0.000. It means that the H0 is rejected and Ha is accepted, and there is a significant correlation among two variables, moreover the two variables are strongly negative correlated.